Preliminary results of open comparative randomized study PHG-M3/P01-09 «ORION» on application of «Phosphogliv» in combined therapy of chronic hepatitis C - M. V. Mayevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate efficacy and safety of «Phosphogliv» in combined therapy of patients with chronic hepatitis C (CHC), that received no previous antiviral treatment.Preliminary results. Four-week application of phosphogliv (glycirrhizinic acid) in a dose of 2,5 g iv 5 times per week, previous to onset of antiviral therapy (AVT) by standard interferon α-2b/ribavirin in the mode corresponding to revealed genotype, has resulted in statistically significant decrease of serum transaminases: alanineaminotransferase (ALT), asparaginaminotransferase (AST) and gamma-glutamyltranspeptidase (GGT) activity in comparison to the group of the patients, that received only standard interferon α-2b/ribavirin (р <002, Wilcoxon T) to the 4-th week of treatment. At this stage of AVT statistically significant decrease of viral load level in comparison to reference value was observed in both groups. Analysis of cases with rapid virologic response (absence of HCV RNA or its level less than 750 copies/ml) within 4 wks of treatment has shown, that only the group phosphogliv/standard interferon α-2b/ribavirin included 3 such cases and that was especially important – all had the 1-st virus genotype. This fact assumes, that phosphogliv can enhance efficacy of standard treatment as adjuvant to antiviral therapy. In both groups usual side effects of AVT developed, which did not require change of treatment mode.Conclusion. Final results of the presented study help to estimate the role of rapid virologic response in the treatment of CHC by standard interferon/ribavirin, to define group of patients for which this mode of therapy is associated with favorable prognosis, and to determine the role of phosphogliv as adjuvant agent in antiviral treatment programs.